Penerapan Model Core (Connecting, Organizing, Reflecting, Dan Extending) Terhadap Peningkatan Hasil Belajar IPA Di Kelas V SDN Roja 3 Ende - Johanes Esse (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
This study departed from the problem of the low science learning outcomes in grade V SDN Roja 3. To overcome this, the CORE model was implemented which aims to improve student learning outcomes. This research is a classroom action research. The research subjects were 11 grade students of SDN Roja 3, totaling 11 people. The data were taken by using test techniques, observation and field notes. Data were analyzed descriptively qualitatively. The results showed that after the application of the CORE model there was an increase in science learning outcomes in grade V SDN Roja 3. This was proven successively from the achievement of completeness of learning outcomes in pre-action by 36 percent and increased to 55 percent in cycle I and reached a maximum of 100 percent in cycle II.